A DNA barcode reference library for the native woody seed plants of Japan. (24th January 2023) - Setsuko, Suzuki; Yoshimura, Kensuke; Ueno, Saneyoshi; Worth, James Raymond Peter; Ujino‐Ihara, Tokuko; Katsuki, Toshio; Noshiro, Shuichi; Fujii, Tomoyuki; Arai, Takahisa; Yoshimaru, Hiroshi
Abstract: DNA barcode databases are increasingly available for a range of organisms, facilitating the wide application of DNA barcode‐based studies. Here we announce the development of a comprehensive DNA barcode reference library of Japanese native woody seed plants representing 43 orders, 99 families, 303 genera and 834 species, and comprising 77.3% of the genera and 72.2% of the species of native woody seed plants in Japan. A total of 6216 plant specimens were collected from 223 sites across the subtropical, temperate, boreal and alpine biomes in Japan with most species represented by multiple accessions. This reference library utilized three chloroplast DNA regions ( rbcL, trnH‐psbA and matK ) and consists of 14, 403 barcode sequences. Individual regions varied in their identification rates, with species‐level and genus‐level rates for rbcL, trnH ‐ psbA and matK based on blast being 57.4%/96.2%, 78.5%/99.1% and 67.8%/98.1%, respectively. Identification rates were higher using region combinations, with total species‐level rates for two region combinations ( rbcL & trnH ‐ psbA, rbcL & matK and trnH ‐ psbA & matK ) ranging between 90.6% and 95.8%, and for all three regions being equal to 98.6%. Genus‐level identification rates were even higher, ranging between 99.7% and 100% for two region combinations and being 100% for the three regions. These results indicate that this DNA barcode reference library is an effective resource for investigations of native woody seed plants in Japan using DNA barcodes and provides a useful template for the development of libraries for other components of the Japanese flora.